Potensi Penerapan Inovasi Teknologi untuk Peningkatan Produksi Padi Lahan Rawa Lebak di Provinsi Jambi - Minsyah, Nur Imdah (Seminar Nasional Lahan Suboptimal, 2022)
Minsyah NI. 2022. The Potential of application of technological innovation to increasing swamp land rice production in Jambi Province. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 208-216. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The increase in rice production confronted: (1) The problem of continuing the conversion of fertile agricultural lands (paddy fields) to uses other than rice farming, and (2) The challenge of increasing sustainable rice production. One of the solutions is optimizing the use of swamp land. Writing this paper aimed to provide an overview of swamp land in Jambi Province in terms of: (1) utilization for rice farming, and; (2). Adoption of Integrated Crop Management (PTT) technology innovations. The use of swamp land in Jambi Province is not optimal, most of it is only planted once a year with local rice, aged within 5-7 months, simple cultivation techniques, minimal maintenance, and production of 2-3 t gkp/ha. One of the innovations to increase rice productivity and production in swamp land is Integrated Crop Management (PTT) for rice. In an effort to accelerate the mass diffusion of PTT rice technology innovations, the Ministry of Agriculture implemented the Integrated Crop Management Field School Program, abbreviated as SL-PTT, the program started in 2008. During this program it has been proven to be able to increase rice productivity. After this program ends, the opportunity to be adopted, fully implemented by farmers and diffused to other places tends to depend on the perceptions of farmers that are formed.